ANALISIS PENILAIAN KINERJA DOSEN MENGGUNAKAN METODE AHP (Studi Kasus : STIKOM Dinamika Bangsa) - Hetty Rohayani (JURNAL AKADEMIKA)
Rapid technological advances in the era of globalization in education, requires decision-makers conducted by an objective and clear. Decision-making faculty performance appraisal using AHP (Analytical Hierarchy Process), is an alternative solution that could dilakukan.At faculty performance appraisal research done by pairwise comparisons between the existing criteria that include teaching, research, service and student assessment. And bring samples based on the results of the questionnaire as a lecturer of the source data. After completing the alternative assessment, the final choice will come recommended from the analysis as the ultimate alternative of faculty performance assessment itself.